(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to the correlations between Zarafshan oasis peasant communities and cattle-breeders’ culture on basis of the theoretical experiment results. The main attention is pointed to Sarazm, Zamonbobo and Toqaytepa memorials and cattle-breeders’ culture affections to their formations and developments.